Implementasi Jual Beli Emas Dengan Sistem Tukar Tambah Di Toko Emas H. ST. Martua Hsb Pasar Sibuhuan Menurut Perspektif Ekonomi Islam - Ida Ayu Lestariyana Hasibuan; H.Amhar Maulana; Nur Jannah Nasution (Institut Nalanda, 2024)
This thesis aims: (1) Implementation of Gold Buying and Selling with an Exchange System at the H Gold Shop. (2) To find out the implementation of buying and selling gold using an exchange system at the H. ST Gold Shop. Martua Hsb Sibuhuan Market according to an Islamic economic perspektive. This research is field research (filed research ) With a qualitative research type . The research subjects were customers, owners and employees of the H.ST Gold Shop. Martua Hsb Sibuhuan Market. Data collection techniques through interviews, observation and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The results of the research show that: (1) ST. Martua Hsb Sibuhuan Market in its implementation, consumers came bring old jewelry that has been worn previously with a purpose want to exchange the old jewelry for new jewelry by bringing proof of jewelry certificate after the gold has been weighed and appraised the price and additional charges per gram, it also depends on the condition of the old gold jewelry. If it is not damaged then it will be wor additional per gram Rp. 20,000 whereas if it is damaged then additional/cut will differ according to the condition of the gold, additional This will be used for cleaning costs. As for the system The payment is agreed upon at the time of the contract before leaving the assembly. (2) Implementation of Gold Buying and Selling with an Exchange System at the H. ST Gold Shop. Martua Hsb Sibuhuan Market according to an Islamic ecomic perspektive, if it is linked to the concept of buying and selling using an exchange system, the terms and conditions of buying and selling have been fulfilled. The process of determining and adding prices is in accordance with the concept of justice in Islamic. So in practice it is in line with the concept of buying and selling with an exchange system where in the transaction the buyer and seller negotiate to get a price that matches the desired price by considering the type and quality of the goods. All terms and conditions of sale and purchase can be realized so that the contract is valid and there is no damage to the contract because both parties are willing and pleased to carry out the transaction